Gender and breeding in tropical forages: A literature review - Pazos Cardenas, Mateo; Triana Ángel, Natalia; Burkart, Stefan (2024)
The integration of gender analysis into plant breeding represents a crucial step towards achieving more equitable and sustainable agricultural systems. Women are key contributors to agriculture and livestock industries, yet their work is often overlooked and poorly compensated. This poster provides an overview of current research efforts, progress made, and challenges encountered in incorporating gender considerations into plant breeding programs, especially focused on tropical forages as one key CGIAR breeding programs. The methodology used was a literature review throughout the scientific production of the CGIAR centers related to these topics. The balance made of some of the reviewed studies led to conclude that, although there are some valuable efforts done in the last two decades, there are also different challenges faced in integrating gender analysis into plant breeding, such as limited resources, institutional barriers, and the need for capacity building among breeders and researchers. As far as the tropical forages and livestock issue, the introduction of gender in breeding discussions shows that women prioritize traits in crops and livestock that help them manage their families' food security and generate income, boosting their economic independence and empowerment. However, sociocultural differences in women’s activities related to livestock and forage systems and useful methodologies to identify relevant traits for them and other marginalized groups are yet to be deepened. These findings are important to prioritize further research on breeding, market dynamics and gender sensitive studies.